2015
DOI: 10.1016/j.juro.2015.07.090
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Patient Centered Interventions on Persistent Urinary Incontinence after Prostate Cancer Treatment: A Randomized, Controlled Trial

Abstract: Study findings show that pelvic floor muscle exercise practice plus symptom self-management in a peer support setting can significantly improve urinary continence and quality of life in patients with prostate cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
52
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(55 citation statements)
references
References 22 publications
0
52
0
1
Order By: Relevance
“…Qualitative synthesis revealed that program content focused only on medical/behavioral management (Foster et al, 2016;Lee et al, 2014;Yun et al, 2012;Zhang et al, 2015) and emotional management (Braamse et al, 2016;Germino et al, 2013;Gil et al, 2006;Mishel et al, 2005;Olesen et al, 2016;Owen et al, 2005;van den Berg et al, 2015). Healthcare professionals should be aware of the importance of role management, including in the family, at work, in communication, and in independent living.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Qualitative synthesis revealed that program content focused only on medical/behavioral management (Foster et al, 2016;Lee et al, 2014;Yun et al, 2012;Zhang et al, 2015) and emotional management (Braamse et al, 2016;Germino et al, 2013;Gil et al, 2006;Mishel et al, 2005;Olesen et al, 2016;Owen et al, 2005;van den Berg et al, 2015). Healthcare professionals should be aware of the importance of role management, including in the family, at work, in communication, and in independent living.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of SMIs (n = 7) dealt with emotional management, including distress management (Braamse et al, 2016;van den Berg et al, 2015), uncertainty management (Germino et al, 2013;Gil et al, 2006;Mishel et al, 2005), empowerment (Olesen et al, 2016), and coping (Owen et al, 2005). Four trials targeted medical/behavioral management, such as fatigue management (Foster et al, 2016;Yun et al, 2012), incontinence management (Zhang et al, 2015), or exercise and diet (Lee et al, 2014). Only one trial (Risendal et al, 2015) applied a multicomponent intervention, combining medical, role, and emotional management.…”
Section: Intervention and Control Conditionsmentioning
confidence: 99%
See 2 more Smart Citations
“…restabelecer a musculatura do esfíncter, deixando as margens dessa discussão os sentidos que os adoecidos elaboram sobre esta experiência. Entretanto, uma evidência é comum em seus resultados, a incontinência urinária está presente em mais de 40% dos homens que se submetem ao tratamento do CP (MAO et al, 2015;ZHANG et al, 2015). Este dado nos leva a refletir que todos os anos muitos homens acometidos pela doença também sofrem com questões identitárias consequentes da incontinência.…”
Section: )unclassified